THE STRATEGY DEVELOPMENT SMEs METAL FROM BUSINESS EFFICIENCY ASPECT AND WELFARE LEVEL OF THE METAL CRAFTSMEN - Gunawan, Diah Setyorini; Ahmad, Abdul Aziz; Gunawan, Ratna Setyawati (Universitas Muhammadiyah Kalimantan Timur, 2024)
This research identifies the profiles of metal craftsmen, analyze the efficiency of metal businesses, and analyze the welfare level of the metal craftsmen in Pasir Wetan Village. The results of this research are expected to support the development of SMEs metal. The research method used was a quantitative research method. The study uses primary data and secondary data. Primary data were obtained from direct interviews with metal craftsmen in Pasir Wetan Village, Karanglewas District, Banyumas Regency. Primary data include data on age, education level, length of business, number of workers used, total income, total production costs, and net income level. Whereas secondary data included monograph data of Pasir Wetan Village, Karanglewas Subdistrict, Banyumas Regency. The analytical method used in this study includes descriptive analysis, business efficiency analysis, and welfare level analysis. Based on the results of the research, we can identify the profiles of metal craftsmen in Pasir Wetan Village. In addition, it can be identified that the metal business in Pasir Wetan Village is efficient and the metal craftsmen in Pasir Wetan Village are in the prosperous category. The government, both the central and local governments, through the relevant ministries or agencies, must always provide assistance and involve SMEs in training so that SMEs can always innovate. Innovations made by SMEs will support efforts to increase efficiency and welfare. In addition, SMEs always need capital and equipment assistance. In the context of efforts to increase the efficiency and welfare of SMEs, the government should ideally include universities and related institutions. The role and cooperation of various parties in an effort to increase the efficiency and welfare of SMEs is expected to facilitate the realization of these efforts.